PENGARUH LIMA MACAM PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN KANDUNGAN SENYAWA AKTIF DAUN SIRSAK (Annona muricata L.) - , GALUH ASRINDA TITI MASITO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research aimed to determine the effect of five kinds treatment of organic fertilizers on the growth and bioactive compounds of soursop leaves (Annona muricata L.). The experiment was conducted in June to October 2013 in Babadan Baru, Depok, Sleman, Yogyakarta. Observation of bioactive compounds was conducted in October to November 2013 in the Chem - mix Pratama Laboratory, Bantul, Yogyakarta. This experiment used Completely Randomized Design (CRD) single factor consisting of five kinds of organic fertilizers i.e., goat manure, cow manure, chicken manure, vermicompost, compost and urea as a control. The results showed that organic fertilizer gave effect as good as anorganic fertilizer for soursop growth. Organic fertilizers gave better effect for bioactive compounds mention flavonoids and tannins of the soursop leaves quantitatively than anorganic with the best result in compost.